PROTECTION AGAINST THE ELECTROMAGNETIC STRENGTH OF THE RADIO WAVES IN COMMUNICATION RADIO NETWORKS: PROTECTION AGAINST THE ELECTROMAGNETIC STRENGTH OF THE RADIO WAVES IN COMMUNICATION RADIO NETWORKS - Vasilev , Dragomir (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
In this paper presents protection methods against Electromagnetic straight of the radio waves in communication radio networks. Examples of personal protective equipment for monitoring EMF when working near transmitting devices. Personal Monitor. When an electric current flows through the human body, cells and tissues prevent the movement of charged particles. The value of the resistance depends on the type and condition of the cells, the value and frequency of the applied voltage and the duration.